Self‐commissioning calculation of dynamic models for synchronous machines with magnetic saturation using flux as state variable. Issue 17 (16th April 2019) - Antonello, Riccardo; Peretti, Luca; Tinazzi, Fabio; Zigliotto, Mauro
Abstract : This paper deals with the non‐linear modelling of synchronous machines by using the flux linkage as a state variable. The model is inferred from a conventional set of measurements where the relation between the currents and the flux linkages in the rotating reference frame (also known as dq reference frame) are known by measurements or estimated through finite‐element simulations. In particular, the contribution of this paper is twofold: first, it proposes a method to extract the non‐linear model information which can be easily implemented in electric drives, without the need of offline post‐processing of the data. Second, it mathematically demonstrates that the method converges to the final result in a stable way. An example based on experimental measurements of the current‐to‐flux look‐up tables of an 11‐kW synchronous reluctance machine is shown, proving the feasibility of the proposed method.